Impacts of the removal of invasive Carpobrotus on spider assemblage dynamics - Braschi, Julie; Hélard, Ophélie; Mazzia, Christophe; Oger, Pierre; Ponel, Philippe; Buisson, Elise (Biodiversity and conservation, 2021)
Mediterranean island biodiversity is threatened by invasive plants, especially by Carpobrotus species. Invasive plant control is a major management tool for the restoration of invaded areas, but the effect of Carpobrotus removal on arthropods is poorly understood. In this study, we evaluate how spider assemblages are influenced by Carpobrotus removal on a Mediterranean island. A Carpobrotus patch was manually uprooted, followed by litter removal between November 2011 and February 2012. A nearby site with native matorral vegetation and no management was also studied. Spider communities were sampled using pitfall traps two years before removal (2010–2011), and then every two years after, between 2013 and 2019. Vegetation at the Carpobrotus site changed from a dense mat of Carpobrotus to a diverse halophilous grassland with some chamaephytes, while it remained stable in the matorral. Spider species richness increased significantly after removal and significant changes in assemblage composition were observed between pre- and post-removal years with a high turnover rate, while spider assemblages remained relatively stable in the matorral. Litter-dwelling spiders with trap strategies like Oecobius navus were the most reduced by Carpobrotus removal, while foliage-dwelling spiders which forage on plants like Xysticus benefited the most, likely due to vegetation opening and diversification of microhabitats. The increase in bare ground cover favoured Aelurillus v-insignatus , Nomisia celerima and Zodarion elegans , which are characterized by an affinity for dry sunny environments. Invasive Carpobrotus removal induced a rapid change (7 years) in spider assemblages as well as an enrichment in taxonomic and functional diversities.